The Impact of Traditional Market Externalities on theSocio- Economy of Traders (Case Study of Klewer Market Surakarta City) - Tedy Setiawan Respati; Ali Zainal Abidin (IECON: International Economics and Business Conference, 2023)
Traditional markets are one of the public facilities whose existence is very important and neededby the community, especially to fulfill one of the basic human needs, namely in terms of food and clothing. In the midst of the development of the Indonesian nation which is more in favor of middleto lower class business actors, the role of traditional markets is very important. The problem in traditional markets is externality. This research uses a qualitative approach with a case study method. Case studies are intended to explore cases in depth through the collection of information from various sources. the type of data uses primary data taken through direct sources without goingthrough intermediaries. data sources are taken from respondents using interview techniques, observation, and documentation (interview list attached) research location in klewer market located at Jalan Dr. Radjiman, No. 5A Gajahan Village, Pasar Kliwon Subdistrict, Surakarta City, Central Java. respondent selection method using purposive sampling. With 10 respondents including 10 klewer market traders in because the researcher considers the sample taken to understand the problem to be studied. Data analysis method using content analysis. The results showed the emergence of positive externalities in terms of physical buildings, toilets, prayer rooms, banking, elevators, escalators, parking lots and access inside and outside. And the emergence of negative externalities in terms of kiosks, decreased sales turnover, and conflicts between buyers.